Genesis of the 1.21 Ga Marnda Moorn large igneous province by plume–lithosphere interaction - Wang, Xuan-Ce; Li, Zheng-Xiang; Li, J.; Pisarevskiy, Sergei; Wingate, Michael (Elsevier BV, 2014)
The 1.21 Ga Marnda Moorn large igneous province (LIP) of the Yilgarn Craton is important for understanding the final breakup of the Nuna (Columbia) supercontinent. However, its petrogenesis is poorly understood owing to the lack of geochemical data. We conducted geochemical analyses of the Gnowangerup–Fraser Dyke Suite, a major part of the Marnda Moorn LIP, and report the first geochemical and Nd isotope data for this LIP. Results of a complementary paleomagnetic study of these dykes will be published elsewhere. Most of the studied dykes consist of predominately tholeiitic and OIB-like dolerite (Group 1) and one arc-like and more felsic dyke (Group 2). Group 1 samples have incompatible trace element compositions similar to those of tholeiitic Hawaiian plume-induced OIB and typical asthenospheric mantle-derived Nd isotopes with ɛNd(t) varying from +3.7 to +7.5, produced mainly within the spinel stability field (<75 km depth). Their source region most likely contains recycled oceanic crust. Samples from the Group 2 dyke are characterized by extremely unradiogenic Nd isotopes with ɛNd(t) of about −12, strong depletion of Nb–Ta–Zr–Hf–Ti, chondritic Nb/Ta ratios (20–18), oversaturated silica, and strong deficiencies in CaO, FeOt, TiO2, and Ni. This implies that the dyke was produced by partial melting of enriched sub-continental lithospheric mantle. The coexistence of OIB- and arc-like end-members but mainly Hawaiian OIB-like tholeiitic mafic dykes, interpreted large-scale asthenosphere upwelling in a very short time, and the large volume of mafic magma, favour a plume origin for the Marnda Moorn LIP. The geochemical and emplacement characteristics are attributed to relief of the lithosphere–asthenosphere boundary across the Yilgarn craton and a complex interplay between the plume, heated lithosphere, normal asthenosphere, and recycled components. We propose a two-stage melting model to explain the geochemical composition and emplacement of the Marnda Moorn LIP. Our plume-lithosphere interaction model is consistent with the occurrence of synchronous ultrahigh-temperature events in the Musgrave Province of central Australia.